David Strau [Strauss] (Tufts Archival Research Center, 2008)
2.5 x 4.25. "David Strau." Produced by: Hof-Photograph Hermann Gnther frher Werderscher Markt No. 6, jezt [sic; now]: Ziethenplatz No. 2, Berlin. These dates are approximate.